1983
DOI: 10.3758/bf03326810
|View full text |Cite
|
Sign up to set email alerts
|

Naloxone-reversible effects of ethanol on passive avoidance behavior in mice

Abstract: Performance impairments were evident, in CD! mice tested in a passive avoidance apparatus, following posttrial intraperitoneal administration of ethanol (1.0 and 2.0 glkg) or morphine (0.5 and 1.0 mglkg), or following posttrial immobilization stress (30 and 60 min). Lower doses of ethanol (0.5 glkg) or morphine (0.25 mglkg), or a shorter immobilization time (15 min) were ineffective. Ethanol, at an ineffective dose (0.50 glkg) enhanced both the effects of morphine and those of immobilization stress. The effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…1981;Kiianmaa etal. 1983;Castellano and Pavone 1984). These independent findings support a potential clinical use of Nx in reversing EtOH intoxication and suggest an involvement of endogenous opioids in the action of EtOH.…”
supporting
confidence: 69%
“…1981;Kiianmaa etal. 1983;Castellano and Pavone 1984). These independent findings support a potential clinical use of Nx in reversing EtOH intoxication and suggest an involvement of endogenous opioids in the action of EtOH.…”
supporting
confidence: 69%
“…Perplexingly, while alcohol appears to ubiquitously enhance declarative memory consolidation in humans (Bruce, Pihl, et al, 1999; Bruce, Shestowsky, et al, 1999; Bruce & Pihl, 1997; Carlyle et al, 2017; Doss et al, 2018; Lamberty et al, 1990; Mueller et al, 1983; Parker et al, 1980, 1981; Tyson & Schirmuly, 1994; Weafer et al, 2016), its effects on consolidation are not as consensual in animal work (Alkana & Parker, 1979; Aversano et al, 2002; Castellano & Pavone, 1983; Castellano & Pavone, 1988; Colbern et al, 1986; de Carvalho et al, 1978). Namely, using passive avoidance tasks and alcohol doses that are twofold to fivefold those used in human work, early rodent work showed that post‐learning alcohol injection enhances (Alkana & Parker, 1979; Colbern et al, 1986), disrupts (Aversano et al, 2002; Castellano & Pavone, 1983, 1988) or does not alter memory consolidation (de Carvalho et al, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…Perplexingly, while alcohol appears to ubiquitously enhance declarative memory consolidation in humans (Bruce, Pihl, et al, 1999; Bruce, Shestowsky, et al, 1999; Bruce & Pihl, 1997; Carlyle et al, 2017; Doss et al, 2018; Lamberty et al, 1990; Mueller et al, 1983; Parker et al, 1980, 1981; Tyson & Schirmuly, 1994; Weafer et al, 2016), its effects on consolidation are not as consensual in animal work (Alkana & Parker, 1979; Aversano et al, 2002; Castellano & Pavone, 1983; Castellano & Pavone, 1988; Colbern et al, 1986; de Carvalho et al, 1978). Namely, using passive avoidance tasks and alcohol doses that are twofold to fivefold those used in human work, early rodent work showed that post‐learning alcohol injection enhances (Alkana & Parker, 1979; Colbern et al, 1986), disrupts (Aversano et al, 2002; Castellano & Pavone, 1983, 1988) or does not alter memory consolidation (de Carvalho et al, 1978). As this evidence suggests that alcohol heterogeneously affects passive avoidance memory consolidation in animals, its relationship to previous (Bruce, Pihl, et al, 1999; Bruce, Shestowsky, et al, 1999; Bruce & Pihl, 1997; Carlyle et al, 2017; Doss et al, 2018; Hewitt et al, 1996; Lamberty et al, 1990; Mueller et al, 1983; Parker et al, 1980, 1981; Scholey & Fowles, 2002; Tyson & Schirmuly, 1994; Weafer et al, 2016) and present work remains, however, unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In one of the conditions of a study that examined the effect on naloxone on posttrial administration of ethanol, Castellano and Pavone (1983) found that 30 or 60 min of immobilization stress following passive avoidance training in control mice produced a performance deficit at testing, whereas a 15-min treatment was without effect. The retrograde effects of immobilization stress (Castellano & Pavone, 1983) and footshock (Experiment 2B of the present study) can be seen as complementary to the anterograde stress-induced SDR found by Morilak et al (1983). However, it should be noted that the relatively mild shock regimen used in the These data are depicted in Figure 3.…”
Section: Discussionmentioning
confidence: 99%